Lean Application and Efficiency of manufacturing firms: An empirical study of manufacturing firms in Rivers State, Nigeria - Benaiah, Karibo Benaiah (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
The increasing demand for speedy delivery of quality products at lower production cost have resulted to new trend in manufacturing to review the gap between input resources inventory and production output inventory. More so, creating competitive niche in the current market environment is now difficult for manufacturers than ever in meeting competitiveness. Consequently, many manufacturing firms are becoming flexible to catch up with the current challenges so as to simultaneously improve quality and productivity. This paper examined the relationship between lean manufacturing and efficiency of 53 manufacturing firms listed with the Manufacturers Association of Nigeria in Rivers State, Nigeria. The questionnaire was used to collect data from respondents and analysed using, mean scores, standard deviations and t-statistic in testing stated hypothesis. It was observed that lean manufacturing has a very strong positive and significant influence on efficiency of manufacturing firms. We recommend that: management of manufacturing firms should set up clear policies on lean implementation and communicate same to staff. Also, managers of manufacturing firms are encouraged to increase its resource commitment to staff training and development so as to inculcate in them skills and knowledge necessary to implement lean practices in within their organisations; therefore, professionalism should be encouraged at all levels of the organization. Again, manufacturing firms should pursue quality consciousness through capability surveillance, in having constant monitoring of suppliers/throughput process to ensure production outputs conforms to product specification and quality standards, should be constantly advocated.